Analysis of Marketing Strategies at Fried Chicken Restaurant Nelongso UPN Branch Using the SWOT Analysis Method - Maisaroh, Siti Sofia; Waluyo, Minto (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
In the current era of globalisation, competition in the business world is very tight in various industries including the culinary industry. It is necessary to have the right marketing strategy to increase sales so that the products sold are more attractive to consumers. This study aims to determine the right marketing strategy at the Nelongso Fried Chicken Restaurant, UPN branch. The method used is SWOT analysis. Based on the results of data processing using the IFAS and EFAS matrices, the total IFAS matrix weighting score is 3.6117. While in the EFAS matrix the total weighting score in the EFAS matrix is 3.8996. The results of the SWOT diagram show that the Nelongso Fried Chicken Restaurant, UPN Branch is in quadrant I, namely the S-O strategy. S-O strategies that can be used include adding the latest menu that is more contemporary, creating interesting content on all social media and adding photo space for customers with a more attractive restaurant design.